2020
DOI: 10.1038/s41598-020-75490-y
|View full text |Cite
|
Sign up to set email alerts
|

A rigorous assessment and comparison of enumeration methods for environmental viruses

Abstract: Determining exact viral titers in a given sample is essential for many environmental and clinical applications, e.g., for studying viral ecology or application of bacteriophages for food safety. However, virus quantification is not a simple task, especially for complex environmental samples. While clonal viral isolates can be quantified with relative high accuracy using virus-specific methods, i.e., plaque assay or quantitative real-time PCR, these methods are not valid for complex and diverse environmental sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(37 reference statements)
2
17
0
Order By: Relevance
“…As a first step towards evaluation of the Videodrop, we precisely determined the concentration of phages using three classical methods. We established that qPCR and EPI provide very similar concentrations, in contrast to a previous study in which the authors found significantly lower concentrations by EPI than qPCR (Kaletta et al 2020). The better agreement between the values obtained by the two methods in our study may have resulted from the use of a more concentrated staining solution, the addition of a flash freezing step to improve the staining, and/or the use of a different microscopic setup.…”
Section: Discussionsupporting
confidence: 55%
“…As a first step towards evaluation of the Videodrop, we precisely determined the concentration of phages using three classical methods. We established that qPCR and EPI provide very similar concentrations, in contrast to a previous study in which the authors found significantly lower concentrations by EPI than qPCR (Kaletta et al 2020). The better agreement between the values obtained by the two methods in our study may have resulted from the use of a more concentrated staining solution, the addition of a flash freezing step to improve the staining, and/or the use of a different microscopic setup.…”
Section: Discussionsupporting
confidence: 55%
“…Quantifying gokushoviruses remains difficult due to methodological biases. Quantification of total viral communities by epifluorescence microscopy and flow cytometry after nucleic acid staining biases against viruses with small genomes and genomes that are single stranded (Tomaru and Nagasaki, 2007; Holmfeldt et al ., 2012; Kaletta et al ., 2020). RCA, which is the main method used to identify ssDNA phage genomes, preferentially amplifies these genomes over those of dsDNA phage, prohibiting inference of the relative abundance of different phage types from sequence data.…”
Section: Introductionmentioning
confidence: 99%
“…NTA and plaque counting form complementary, tandem measurements, which together reveal richer insights into the evolution of the phage suspension titre and aggregation state, compared to either technique alone. NTA yields individual particle information across statistically significant sample sizes (Malvern, 2017) and has been demonstrated for the study of bacteriophage (Hsiao et al, 2016; Kaletta et al, 2020) and viral suspensions (Du et al, 2010; Szakács et al, 2018). In contrast, dynamic light scattering (DLS) yields ensemble averages of diffusion coefficients (and extrapolated distributions of hydrodynamic radius).…”
Section: Discussionmentioning
confidence: 99%